2003
DOI: 10.1111/j.1095-8649.2003.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of gag in the southern Gulf of Mexico

Abstract: Aspects of the reproductive biology of gag Mycteroperca microlepis in the southern Gulf of Mexico were studied by following seasonal variations in the gonado-somatic index and through histological examination of gonads. Gag were collected from inshore and offshore waters of the Campeche Bank, Yucatan, Mexico, between April 1996 and December 2001. This species is a protogynous hermaphrodite, and appeared to be depth-size distributed. The smallest gag (9-49 cm L F ) collected were all juvenile females, and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 9 publications
5
22
0
1
Order By: Relevance
“…Similarly, Bullock and Murphy (1994) and Collins et al (1997) indicated that transitional specimens have typically represented less than 1-2% of samples. Protogynous hermaphroditism in M. fusca is in line with the pattern of sexual reversal described in other species of the genus, such as M. rubra in Mediterranean waters (Heemstra and Randall, 1999), Mycteroperca phenax Jordan and Swain, 1884 along the coast of the west-central Atlantic (Harris et al, 2002), M. bonaci (Brulé et al, 2003a), Mycteroperca intertitialis (Poey, 1860) (Bullock and Murphy, 1994;), and M. microlepis (Crabtree and Bullock, 1998;Collins et al, 1997;Brulé et al, 2003b) and Mycteroperca tigris (Valenciennes, 1833) (García-Arteaga et al, 1999) in the waters of the east Atlantic, which clearly reveal this as a characteristic of the genus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Bullock and Murphy (1994) and Collins et al (1997) indicated that transitional specimens have typically represented less than 1-2% of samples. Protogynous hermaphroditism in M. fusca is in line with the pattern of sexual reversal described in other species of the genus, such as M. rubra in Mediterranean waters (Heemstra and Randall, 1999), Mycteroperca phenax Jordan and Swain, 1884 along the coast of the west-central Atlantic (Harris et al, 2002), M. bonaci (Brulé et al, 2003a), Mycteroperca intertitialis (Poey, 1860) (Bullock and Murphy, 1994;), and M. microlepis (Crabtree and Bullock, 1998;Collins et al, 1997;Brulé et al, 2003b) and Mycteroperca tigris (Valenciennes, 1833) (García-Arteaga et al, 1999) in the waters of the east Atlantic, which clearly reveal this as a characteristic of the genus.…”
Section: Discussionmentioning
confidence: 99%
“…The growing oocytes were classified according to the six histological stages proposed by Moe (1969) specifically for groupers, modified by Brulé et al (1999) for Mycteroperca species and extensively used for this genus (Brulé et al, 2003a, b;Tuz-Sulub et al, 2006): I, primary oocyte; II, immature oocyte; III, oocyte in primary vitellogenesis; IV, oocyte in early secondary vitellogenesis; V, oocyte in late secondary vitellogenesis; VI, mature and hyaline oocyte. The criteria described by Shapiro et al (1993) for grouper and by Brulé et al (2003b) for Mycteroperca species, and extensively applied as criteria in grouper species (Sadovy and Colin, 1995;Rhodes and Sadovy, 2002), were used to distinguish a resting mature female from an immature female based on the presence of muscle bundles remnants and connective tissue surrounding blood vessels. Testes were classified according to the most advanced stage of spermatogenesis observed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was clearly observed due to the presence of a gap in the oocyte size frequency distribution between hydrated oocytes and advanced yolked oocytes in the actively spawning phase BrownPeterson et al, 2011). Multiple spawning is a condition reported for many other coral reef fish species, such as Nassau grouper Epinephelus striatus (Bloch, 1792) (Colin, 1992), inshore coral trout Plectropomus maculatus (Bloch, 1790) (Ferreira, 1993), gag Mycteroperca microleps (Goode & Bean, 1879) (Brulé et al, 2003), coney Cephalopholis fulva (Linnaeus, 1758) (Trott, 2006), white grunt Haemulon plumieri (Lacépède, 1801) (Palazón-Fernandéz, 2007;Shinozaki-Mendes, 2013a, b), and mutton hamlet Alphestes afer (Bloch, 1793) (Marques and Ferreira, 2011). Overall, coral reef fish species present a variety of complex spawning systems, but among them two major groups are generally observed: (1) demersal spawners, showing a synchrounous oocyte development and total spawning, represented mainly by species of the families Gobiidae, Blenniidae and Pomacentridae; and (2) pelagic spawners, exhibiting asynchronous oocyte development and spawning in portions, represented by families such as Lutjanidae, Haemulidae, Carangidae, Mullidae, and Gerreidae (Rong-Quen, 2000;Petersen and Warner, 2002).…”
Section: Discussionmentioning
confidence: 99%